2002
DOI: 10.1097/00043764-200202000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Medical Surveillance of Clandestine Drug Laboratory Investigators

Abstract: Law enforcement officers investigating clandestine drug laboratories may be exposed to a wide range of hazardous chemicals. This study was conducted to determine the extent of persistent health effects seen in California drug laboratory investigators after occupational exposure. Study participants with a minimum of 1 year of laboratory investigations completed a questionnaire evaluating occupational and personal health history and consented to review of their medical surveillance examinations and administrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Both production methods utilize a strong base, a solvent, and hydrochloric acid to remove the methamphetamine from solution and both methodologies can produce large quantities of relatively high purity methamphetamine. 4,8 The Birch reduction method has become very popular since the late 1990s due to the low cost and high Figure 1. Illustration of the structural similarities between the ephedrine, pseudoephedrine, and methamphetamine.…”
Section: Manufacturing Methodsmentioning
confidence: 99%
“…Both production methods utilize a strong base, a solvent, and hydrochloric acid to remove the methamphetamine from solution and both methodologies can produce large quantities of relatively high purity methamphetamine. 4,8 The Birch reduction method has become very popular since the late 1990s due to the low cost and high Figure 1. Illustration of the structural similarities between the ephedrine, pseudoephedrine, and methamphetamine.…”
Section: Manufacturing Methodsmentioning
confidence: 99%
“…PPE may be available on a planned raid of a clandestine laboratory, however, the level of chemical exposure is often not known and the need for "speed and surprise" and the possibility of hostile actions and "booby-traps" (66) from occupants of the premises during the raid limit use of PPE (63). Some guidance is available (64,67) for emergency medical personnel in relation to the identification and management of exposures in clandestine laboratories, however, protocols adopted by various members of police, investigators, fire-fighters and medical staff are specific to these organisations and may not consider these aspects.…”
Section: First-responders and Forensic Investigatorsmentioning
confidence: 99%
“…However, they may include: neurochemical changes in areas of the brain that are associated with learning, potentially affecting cognitive function, behaviour, motor activity and changes in avoidance responses (106); psychotic, physiological and behavioural/developmental effects that include violent behaviour, depression, irritability, hallucinations, mood swings, paranoia, mood and sleep disorders that are associated with exposure to, or use of, methamphetamine (75,(106)(107)(108)(109)(110); as well as effects associated with exposure to the range of chemicals present, that includes cancer and effects on respiratory, renal, hepatic, neurological, developmental and reproductive systems (5). Exposures by first-responders have resulted in chronic respiratory (including asthma and significantly decreased lung function), gastrointestinal, neurological and immune system effects (29,63,102,111).…”
Section: Chronic Effectsmentioning
confidence: 99%
“…In a study of 59 law enforcement personnel surveyed in Washington state, headache, respiratory, mucous membrane, and skin irritation symptoms were common (Burgess, Barnhart & Checkoway 1996). In another study, 40 California clandestine lab investigators were found to have decrements in annual spirometry values similar to decrements observed in continuing smokers (Burgess et al 2002). The study also reported that on average, investiga tors spent 11 minutes during the entry phase, 30 minutes during the assessment phase, and 194 minutes during the processing phase.…”
Section: Exposure Among First Responders and Law Enforcementmentioning
confidence: 91%